Sarcoidosis and Polymethyl Methacrylate (PMMA) Granulomas following COVID-19 Vaccination (ChAdOx1): Successful Treatment with Tofacitinib - Ianhez, Mayra; Miot, Hélio A [UNESP]; Caetano, Lívia V.N.; De Paula, Henrique Moura; Freire, Giselle G.S.; Torres, Pedro P.T.S. (Wolters Kluwer, 2024)
Sarcoidosis and complications related to fillers have been reported following the COVID-19 vaccination. Additionally, cutaneous sarcoidosis has been observed around polymethyl methacrylate (PMMA) injection sites. Foreign-body reactions to PMMA can occur simultaneously with systemic sarcoidosis, suggesting a shared pathogenic mechanism between both conditions. To report a case of sarcoidosis and PMMA granulomas following COVID-19 vaccination (ChAdOx11), successfully treated with tofacitinib. We present a 59-year-old woman who developed systemic sarcoidosis and a granulomatous reaction to PMMA filler following the COVID-19 vaccination (ChAdOx11). Notably, both PMMA and the vaccine were potential triggers for sarcoidosis. Treatment with tofacitinib produced marked improvement in both the cutaneous and pulmonary involvement of sarcoidosis and the granulomatous reaction to PMMA. This successful outcome suggests tofacitinib, a pan-JAK inhibitor, an alternative treatment for cutaneous and systemic sarcoidosis, as well as a potential therapy for granulomatous complications of dermal fillers, such as PMMA.
Keywords: Aesthetic dermatology; COVID-19; granuloma; Janus kinase inhibitors; polymethyl methacrylate; sarcoidosis